2009
DOI: 10.1111/j.1476-4431.2009.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an abdominal fluid scoring system determined using abdominal focused assessment with sonography for trauma in 101 dogs with motor vehicle trauma

Abstract: Initial and serial AFAST with applied AFS allowed rapid, semiquantitative measure of free abdominal fluid in traumatized patients, was clinically associated with severity of injury, and reliably guided clinical management. Where possible, AFAST and AFS should be applied to the management of blunt trauma cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
175
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(181 citation statements)
references
References 50 publications
4
175
0
2
Order By: Relevance
“…8 This study concluded that initial and serial A-FAST with applied AFS allowed rapid and semiquantitative measure of free abdominal fluid in traumatized patients, was clinically associated with severity of injury, and reliably guided clinical management. 8 Serial examination is recommended to assess the degree of haemorrhage and monitor its progression or resolution. 8 However, caution is recommended in the absence of fluid (AFS ¼ 0).…”
Section: Focused Emergency Ultrasoundmentioning
confidence: 95%
See 1 more Smart Citation
“…8 This study concluded that initial and serial A-FAST with applied AFS allowed rapid and semiquantitative measure of free abdominal fluid in traumatized patients, was clinically associated with severity of injury, and reliably guided clinical management. 8 Serial examination is recommended to assess the degree of haemorrhage and monitor its progression or resolution. 8 However, caution is recommended in the absence of fluid (AFS ¼ 0).…”
Section: Focused Emergency Ultrasoundmentioning
confidence: 95%
“…1 -7 One of the major advantages of FAST, in the veterinary clinical environment, is that the protocol can be performed in minutes 8 -11 with minimal patient restraint and simultaneously with other concurrent interventions/ tests by veterinary surgeons who are not radiologists or experienced in ultrasonography. 8,9,12 Abdominal-FAST Intra-abdominal injury is difficult to detect and can potentially be fatal such as in cases of uncontrollable haemorrhage. Computed tomography (CT) is becoming the imaging modality of choice for intra-abdominal injury in veterinary medicine.…”
Section: Focused Emergency Ultrasoundmentioning
confidence: 99%
“…24 Alternatively, if the packed cell volume (PCV) of the fluid is increasing or nears the PCV found in the peripheral blood, ongoing hemorrhage should be suspected. 3 Additionally, the AFS was associated with severity of injury; dogs with AFS scores of 3 or 4 were more likely to have a significantly lower PCV and total plasma protein as well as increased serum concentrations of ALT. 24 Using an abdominal FAST technique (described earlier), one study evaluated an abdominal fluid scoring system, or AFS.…”
Section: Diaphragmatic Rupturementioning
confidence: 95%
“…[1][2][3] In a study of 235 canine cases of blunt trauma, 91.1% of all blunt trauma cases were secondary to motor vehicular accidents. [1][2][3] In a study of 235 canine cases of blunt trauma, 91.1% of all blunt trauma cases were secondary to motor vehicular accidents.…”
Section: Blunt Traumamentioning
confidence: 99%
See 1 more Smart Citation